Graphic Design Vietnam - Problems and Solutions - Ngoc , Nguyen Hong; Huong, Nguyen Thi Lan (Journal of Ecohumanism, 2024)
The field of design in the world in general, and Graphic Design in particular tends to converge and interfere strongly with other art disciplines (such as fine arts, movies, and music...). Graphic design will flourish with cutting-edge technology, and this will certainly continue to grow in the future. Graphic design today needs to identify several common concerns with themes: boundaries and interlinkages between the arts and graphic design, the importance of content, and impact of advanced technology, the desire for emotional connection, limitations in creativity due to, imposed design software, the uncertainty of commercialization, the need to simplify the design to increase the speed at which information is perceived by visual cues, and, ultimately, the need to be ethical in design. The above problems have never been raised for the Vietnamese contemporary graphic design industry. The study of Contemporary Graphic Design in the development of Vietnamese culture is necessary to create a connection between the past and the present in terms of culture and spirit, because before or after, a production includbelongso belongs to a particular ethnic group.